Increasing the effectiveness of teaching differential equations based on context-based teaching (MMIT Proceedings, 2024)
In this thesis describes the methodological conditions for achieving educational effectiveness by applying contextual learning, innovative and information technologies to lectures and practical classes in teaching the subject “Differential Equations” in a higher educational institution.